Bandstop frequency-selective structures based on stepped-impedance loop resonators : design, analysis, and measurement - Wang, Wensong (2020)
A new dual-polarized and dual-band second-order bandstop 3-D frequency-selective structure (FSS) is proposed with arbitrary band ratio. Compared with the square loop, the stepped-impedance (SI) loop resonator performs at lower basic resonant frequency and increases the first spurious resonant frequency. Different half-wavelength SI loop resonators are analyzed, compared, and employed to design single/dual-band 3-D FSSs under TE polarization. A double-sided SI loop resonator with via holes is presented for constructing a dual-polarized single band FSS. By adjusting widths of low characteristic impedance sections, the FSS's band can be expanded into dual bands. Detailed analysis of the coupling between both identical resonators in series is provided for understanding the relationships between subresonators. In addition, the equivalent circuit models are developed to explain the operating principle and analyze parameter effects. The proposed FSS prototype is fabricated and then measured to verify the design methodology. The measured results agree with the simulated data and exhibit a dual-polarized and stable second-order bandstop response under different incident angles up to 30°. The thickness of the structure is 23% of the free-space wavelength at the first center frequency, and the center frequency ratio of both stopbands is only 1.08.